Rainfall-runoff modelling using improved machine learning methods: Harris hawks optimizer vs. particle swarm optimization - Tikhamarine Y.; Souag-Gamane D.; Ahmed A.N.; Sammen S.S.; Kisi O.; Huang Y.F.; El-Shafie A. (Elsevier B.V., 2023)
Autocorrelation; Biomimetics; Forecasting; Multilayer neural networks; Particle swarm optimization (PSO); Rain; Runoff; Support vector machines; Swarm intelligence; Autocorrelation functions; Cross-correlation function; Hyper-parameter optimizations; Least squares support vector machines; Machine learning methods; Partial autocorrelation function; Rainfall - Runoff modelling; Rainfall-runoff relationship; Learning systems; accuracy assessment; autocorrelation; hydrological cycle; machine learning; numerical method; optimization; rainfall-runoff modeling; Parabuteo